(untitled) (Bangladesh Journal of Child Health, 2018)
Background: Seizures are common following perinatal asphyxia and may exacerbate secondary neuronal injury. Barbiturate therapy has been used for infants with perinatal asphyxia in order to prevent seizures. However, barbiturate therapy may adversely affect neurodevelopment leading to concern regarding its aggressive use in neonates. The objective of the study was to determine the effect of administering prophylactic barbiturate therapy on seizure control and mortality in term neonates following perinatal asphyxia. Methodology: This was a randomized controlled trial (RCT) of prophylactic phenobarbitone therapy in term asphyxiated neonates without clinical evidence of seizures when compared to controls conducted in the neonatal ward of Sher-e-Bangla Medical College Barisal from 1st January 2016 to 30th June 2016. Results: Among the 100 neonates equally divided into two groups, there was no significant difference found in clinical outcome e.g. seizures (8% vs. 12%, p > 0.05), neurological abnormality at discharge (10% vs. 14%, p >0.05), mortality (12% vs. 14%, p >0.05) and major neurological disability (14% vs. 18%, p >0.05). Conclusion: In this study, prophylactic phenobarbitone therapy did not significantly prevent seizures in asphyxiated neonates. Bangladesh J Child Health 2017; VOL 41 (3) :165-169